Evaluation of the dumpsite location and waste management of the Kharkhorin soum, Uvurkhangai province, Central Mongolia: Өвөрхангай аймгийн Хархорин сумын хогны цэгийн байршлын үнэлгээ ба хог хаягдлын менежмент - Tsolmongerel, Uyanga; Batjargal, Barsaa; Batsuren, Dorjsuren; Bolat, Altanguli; Tsogoo, Bilguun; Chonokhuu, Sonomdagva (Geographical Issues, 2024)
This study evaluated the municipal waste disposal site location in Kharkhorin soum of Uvurkhangai province, identified a suitable location for a new landfill site, and carried out an analysis of municipal solid waste statistical data for the purpose of identifying waste management measures. The statistical data of municipal waste of Kharkhorin soum for 2019-2023 were used in this research. The dumpsite location of the Kharkhorin soum was evaluated with the Full Permutation Polygon Synthetic Indicator (FPPSI) method by using 15 criteria. The dumpsite of the Kharkhorin soum does not meet the 4 criteria, moderately meets the 4 criteria, fully meets 7 criteria out of 15, and in terms of heavy metal pollution, no pollution was detected in the dumpsite soil samples. The synthetic indicator of the dumpsite is 0.432, which falls into level 3. Regarding municipal solid waste management of the Kharkhorin soum, the amount of waste generation constantly increases, of which 38.9 percent of total MSW was generated in the ger area, 18.8 percent was generated in the commercial sector, 18.1 percent was generated in the apartment area, while 8.1 percent was collected from the streets, 16 percent was collected from other places. In the last two years, 2.1 percent of total waste was reused and recycled. Regarding waste composition, 82 percent of the MSW was non-segregated waste, while the least generated waste types were e-waste, food waste, and vehicle waste.